Twinning and major birth defects, National Birth Defects Prevention Study, 1997–2007. Issue 11 (20th June 2016) - Dawson, April L; Tinker, Sarah C; Jamieson, Denise J; Hobbs, Charlotte A; Berry, R J; Rasmussen, Sonja A; Anderka, Marlene; Keppler-Noreuil, Kim M; Lin, Angela E; Reefhuis, Jennita
Abstract : Background: Twinning has been associated with many types of birth defects, although previous studies have had inconsistent findings. Many studies lack information about potential confounders, particularly use of fertility treatment. Our objective was to assess the association between twinning and birth defects in the National Birth Defects Prevention Study (NBDPS). Methods: We used data from the NBDPS, a population-based, case–control study of major birth defects in the USA, to evaluate associations between twinning and birth defects. The study population included mothers of twin and singleton controls (live-born infants without major birth defects), and cases (fetuses or infants with a major birth defect) born October 1997–December 2007. Adjusted ORs and 95% CIs were estimated using multivariable logistic regression stratified by use of fertility treatment. Twin sex-pairing data and a simulation approach were used to estimate the zygosity of twins. Results: In the unassisted conception stratum, we observed significant positive associations between twinning and 29 of 45 defect groups. The largest effect estimates were observed for multiple ventricular septal defects and cloacal exstrophy. Among mothers reporting any use of fertility treatments, we observed a significant association with twinning for 5 of 25 defect groups, with the largest effect estimates for hypoplastic left heart syndrome and omphalocele. OR estimates in the estimated monozygotic stratum were generally further from the null than in the dizygotic stratum. Conclusions: Compared with singletons, a wide range of birth defects are significantly more common among twins. Birth defect risk in twins may be differential by use of fertility treatment.